Pembelajaran Ranah Psikomotor berbasis Realistic Mathematics Education untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Sari, Tita Tanjung; Cahyono, Anang Hadi (Pedagogik Journal of Islamic Elementary School, 2022)
Critical thinking skills can be practiced by using psychometric realistic math-based learning by implementing an application of "fun math". This study aims to understand the students' critical thinking skills on geometry topics. A quasi-experimental is used on one group of pretests – posttest design. The instruments of this study are critical thinking ability observation sheets and the psychomotor ability evaluation sheets. The subject of this study involves 6 students from the fifth-class year of primary school in SDN Soddara II, Sumenep of East Java province. The data analysis results indicate a learning application of realistic math-based learning through "fun math" on the topic of space building can improve the students’ critical thinking skills, shown by the average score of five indicators. The highest average value (2.4), the indicator of providing a simple explanation and draw conclusions (2.3), are in the good category. The indicator of estimating and providing alternative solutions (2.1), and providing further consideration (2.025) with an average category. The students' critical thinking skills improve on how they are expressing opinions, giving alternative thoughts, unlocking new ways, and presenting them based on the facts that they are able to deliver alternative solutions to create new ideas.